Challenging gender hierarchies in narratives of the nation: representations of women in Zintgraff and the Battle of Mankon and Hard Choice - Nkealah, N.; Oluwasuji, O.G. (My University, 2020)
Abstract Ideas of nationalisms as masculine projects dominate literary texts by African male writers. The texts mirror the ways in which gender differentiation sanctions nationalist discourses and in turn how nationalist discourses reinforce gender hierarchies. This article draws on theoretical insights from the work of Anne McClintock and Elleke Boehmer to analyse two plays: Zintgraff and the Battle of Mankon by Bole Butake and Gilbert Doho and Hard Choice by Sunnie Ododo. The article argues that women are represented in these two plays as having an ambiguous relationship to nationalism. On the one hand, women are seen actively changing the face of politics in their societies, but on the other hand, the means by which they do so reduces them to stereotypes of their gender. Keywords: ambiguity; gender hierarchy; nationalism; feminism; masculinity; narratives of the nation